Profitability and Capital Structure and its Impact on Dividend Policy: A Case Study of Real Estate Property Sectors Listed in Indonesia Stock Exchange 2013-2017 - Imam Heryanto; Achmad Setya Nugraha (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2019)
The property sector is one of the industrial sectors that has a vital role as an indicator of a country's economy condition. The level of industrial development can be seen from the dividend policy in the form of cash dividends given to the shareholders as a return of operational activities. The amount of provided cash dividends is one of the essential considerations for investors in investing their capitals in companies. Some previous studies show that the profitability and capital structure has a significant role in influencing dividend policy. Thus, this study examines the influence of these two factors on dividend policy. The results of the study prove that profitability has a positive and significant effect, with a regression coefficient of 0.610. Meanwhile, the capital structure has a negative and significant effect, with a regression coefficient of -0.030. The total effect value of the two variables is 68%, while the remaining 32% comes from the other variables that are not used in the research model.